2003
DOI: 10.1016/s0002-9440(10)63561-4
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of Macrophage Activation in Anti-Thy-1.1 Nephritis

Abstract: Macrophages infiltrating glomeruli in telescoped nephrotoxic nephritis are programmed. The purpose of this study was to assess whether macrophages infiltrating glomeruli of rats with passively induced injury become similarly programmed, and to determine whether macrophage commitment is an early event. Glomerular macrophages isolated from rats with resolving and proliferative anti-Thy-1 nephritis were examined for nitric oxide (NO) generation and expression of lysosomal hydrolases. After a single injection of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
21
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 30 publications
2
21
0
Order By: Relevance
“…Programmed unresponsiveness focuses activation of individual macrophages in a particular direction not only in vitro but also in vivo as demonstrated in models of glomerulonephritis (7,8). Consequently, it is not surprising that macrophages infiltrating inflamed glomeruli can be activated in different ways, presumably stochastically as a result of their initial cytokine contact in the complex microenvironments within inflamed tissue (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Programmed unresponsiveness focuses activation of individual macrophages in a particular direction not only in vitro but also in vivo as demonstrated in models of glomerulonephritis (7,8). Consequently, it is not surprising that macrophages infiltrating inflamed glomeruli can be activated in different ways, presumably stochastically as a result of their initial cytokine contact in the complex microenvironments within inflamed tissue (8).…”
mentioning
confidence: 99%
“…Consequently, it is not surprising that macrophages infiltrating inflamed glomeruli can be activated in different ways, presumably stochastically as a result of their initial cytokine contact in the complex microenvironments within inflamed tissue (8). Understanding the molecular mechanisms for such unresponsiveness could unlock new therapeutic approaches and here we have examined the potential role of one of the prime candidates -suppressors of cytokine signaling (SOCS) proteins.…”
mentioning
confidence: 99%
“…Macrophages in a different microenvironment display a wide diversity in terms of their function and morphology (Minto et al, 2003;Liu et al, 2005a). The heterogeneity of macrophages may be important for the diversity, flexibility and validity of innate and adaptive immune responses to all kinds of stimuli (Kaufmann and Schaible, 2005).…”
mentioning
confidence: 99%
“…Anti-Thy1.1 GN, induced by the injection of anti-Thy1.1 monoclonal antibody (mAb) 1-22-3, is commonly used as the model of human MsPGN (19 -21). It is reported that, the accumulation of macrophages and T lymphocytes into glomeruli is one of the hallmarks of anti-Thy1.1 GN and plays an important pathogenetic role (22). Indeed, the involvement of ED3 + macrophages and CD4 + T helper lymphocytes in the development of the anti-Thy1.1 GN model induced by the injection of mAb 1-22-3 has been reported.…”
Section: Introductionmentioning
confidence: 99%